Personality Detection of Twitter Social Media Users using the Support Vector Machine Method - Salsabila Anza Salasa; Warih Maharani (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Personality is a person's psychological tendency to carry out certain social behaviors, whether in the form of feelings, thoughts, attitudes and will or actions. Big Five is the most popular and widely used personality model, therefore this proposal uses the Big Five Personality model. In this technological era, humans interact using social media. One of the fastest growing social media is Twitter. Twitter is a social media used by all groups. Every human being has a different personality. Personality detectors are needed for employee recruitment to dig up information about the personality of prospective employees. So personality detection or BigFive Personality can be done through tweets that are shared on Twitter. With this, it is necessary to detect personality using the Support Vector Machine (SVM) method. From the results of the study, it was found that the maximum performance parameter combination in detecting personality on Twitter users was a combination of Linear parameters and C = 10 which obtained an accuracy of 0.979. The data used is the result of crawling on the Twitter site with 146 user usernames and 38853 tweets.